ANALISA KUALITAS LIMBAH CAIR RUMAH SAKIT SEMBIRING, DELI TUA - Barus, Bunga Rimta (Jurnal Inovasi Kesehatan Masyarakat, 2019)
Analysis of Liquid Waste Quality in Public Hospitals It is very important to prevent the danger of disease. This research was conducted to find out the waste of Sembiring Deli Tua Hospital in the District of Deli Tua before being processed (Inlet) in terms of wastewater quality standards. Analyzing the quality of liquid waste is done by examining samples in the Health Laboratory for chemical parameters including pH, BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), TSS, free NH, and phosphate and Total E.Coli. Measurements are carried out by laboratory testing to analyze the quality or quality of wastewater disposal that is seen whether it is in accordance with the quality standards of liquid waste for hospital activities according to the decision of the state minister of environment of the Republic of Indonesia. With the discovery of wastewater parameters that do not meet the requirements, it is expected that the Sembiring Deli Tua General Hospital must continue testing all parameters at the monitoring point.